PENGARUH KUALITAS SUMBER DAYA MANUSIA TERHADAP RISIKO KEGAGALAN PENCAPAIAN KINERJA MENGGUNAKAN METODE FAULT TREE ANALYSIS (Studi Kasus : Proyek Pembangunan RSPTN Universitas Jember) - Wulandari, Diah Ayu Restuti; Trisiana, Anita; Kusuma, Naila Su'adiyah Udhma; Tistogondo, Julistyana (Fakultas Teknik, Universitas Wiraraja, 2025)
The State University Hospital Construction Project (RSPTN) at the University of Jember exhibits high complexity in its implementation, involving various factors that have the potential to impact the quality of Human Resources (HR) and the risk of performance failure. This study aims to identify failure risks, evaluate dominant factors affecting Human Resource (HR) quality, and formulate risk mitigation strategies. The Fault Tree Analysis (FTA) method is used to systematically analyze the root causes of the problems. The results of the study indicate that the dominant factors contributing to failure are a lack of awareness regarding job responsibilities, poor coordination, and limited worker experience, with the highest Severity Index (SI) value recorded at 99,67%. Recommended mitigation measures include technical training, certification, strict supervision, and the implementation of a reward and punishment system. With appropriate mitigation strategies, failure risks can be reduced, and project performance can be improved.